Transporte pùblico complementar de passageiros: um estudo de caso em Betim - Ivan Luiz Vieira de Araujo (2012)
Public passenger transport plays a crucial role in the social and economical development of a country. Given its importance, it is in Brazil regulated and controlled by the government (e.g., agencies, state departments and municipal companies). Nevertheless, regulation andcontrol have not prevented the rise of illegal passenger transport in several cities in Brazil. This thesis reports on the results of a case study regarding the Low-Capacity Passenger Transport System of Betim, a municipality in the State of Minas Gerais. This system was created to meet the demand that had not been met by the conventional transport system and concomitantly to overcome the problems brought about by illegal transport in the city. The study focuses on social and economical features of the system, operators and users profiles and perceptions of the system, and an understanding of variables mobility, accessibility andcosts. Results show that the low-capacity passenger transport system plays a crucial role with a significant share of the public transport system in Betim. It contributes to enhance service quality at operational costs virtually similar to those incurred in the conventional passengertransport system. The depiction of the actors involved in the system (Le., users and licensed operators/drivers) and the understanding of their opinions on the system quality can serve as an input for the transport agency, TRANSBETIM, to develop policies that meet the interestsof both users and operators.